Economic analysis of Imazapyrresistant maize technology for small farm households in western Kenya - Mignouna, Djana B.; Manyong, Victor M.; Mutabazi, K.D.; Senkondo, E.; Madulu, R.B.; Labintan, C.A.; Akinola, Adebayo A. (2012)
Farmers in western Kenya are still facing the problem of Striga, the major constraint to cereal production threatening food security of thousands of poor farming households. Some Striga species also attack tropical legumes hence further augmenting protein malnutrition of vulnerable younger children. Imazapyrresistant maize (IRM) technology is being promoted as a response to the increasing Striga problem. The overall objective was to carry out an economic analysis of IRM, novel technology for Striga control to improve maize production in western Kenya. A multistage sampling technique was used to select a total of 600 households from Nyanza and Western provinces for this study. Gross margins and cost to benefit ratios were used as the main tools in data analysis. Evaluation of the use of IRM indicated that the technology is profitable and viable. Encouraging IRM use by farmers can improve food production and therefore is relevant to food policy decisions.